Assessment of bidirectional relationships between circulating cytokines and periodontitis: Insights from a mendelian randomization analysis - Huang, Shi-Jia; Li, Rong; Xu, Shuo; Liu, Yuan; Li, Sheng-Hui; Duan, Sheng-Zhong (Frontiers in Genetics, 2023)
Background: The purpose of this Mendelian randomization (MR) study was to assess the causal relationship between circulating cytokines and periodontitis. Materials and methods: Based on the aggregated statistics of the largest publicly available genome-wide association study (GWAS), we applied a bidirectional two-sample MR. MR analyses were conducted using Inverse variance weighted (IVW), Robust Adjusted Profile Score (RAPS), Maximum likelihood (ML), Weighted median and MR-Egger, and results obtained from IVW served as the primary outcome. Cochran Q test was used to test the heterogeneity. MR-Egger intercept test and MR polymorphism residual and outlier test (MR-PRESSO) were used for polymorphism analysis. Leave-one-out sensitivity and funnel plots were used for sensitivity analysis. Results: The IVW method indicated that interleukin 9 (IL9) had a positive causal relationship with periodontitis [odds ratio (OR) = 1.199, 95% confidence interval (CI) = 1.049–1.372, p = 0.008], and interleukin 17 (IL17) had a negative causal relationship with periodontitis (OR = 0.847, 95% CI = 0.735–0.976, p = 0.022). In bidirectional MR, periodontitis was not causally related to any of the cytokines in our study. Conclusion: Our findings provided evidence in support of potential causal associations between circulating IL9/IL17 and periodontitis.